A sphingolipid mechanism for behavioral extinction. Issue 4 (15th March 2016) - Huston, Joseph P.; Kornhuber, Johannes; Mühle, Christiane; Japtok, Lukasz; Komorowski, Mara; Mattern, Claudia; Reichel, Martin; Gulbins, Erich; Kleuser, Burkhard; Topic, Bianca; De Souza Silva, Maria A.; Müller, Christian P.
Abstract: Reward‐dependent instrumental behavior must continuously be re‐adjusted according to environmental conditions. Failure to adapt to changes in reward contingencies may incur psychiatric disorders like anxiety and depression. When an expected reward is omitted, behavior undergoes extinction. While extinction involves active re‐learning, it is also accompanied by emotional behaviors indicative of frustration, anxiety, and despair (extinction‐induced depression). Here, we report evidence for a sphingolipid mechanism in the extinction of behavior. Rapid extinction, indicating efficient re‐learning, coincided with a decrease in the activity of the enzyme acid sphingomyelinase (ASM), which catalyzes turnover of sphingomyelin to ceramide, in the dorsal hippocampus of rats. The stronger the decline in ASM activity, the more rapid was the extinction. Sphingolipid‐focused lipidomic analysis showed that this results in a decline of local ceramide species in the dorsal hippocampus. Ceramides shape the fluidity of lipid rafts in synaptic membranes and by that way can control neural plasticity. We also found that aging modifies activity of enzymes and ceramide levels in selective brain regions. Aging also changed how the chronic treatment with corticosterone (stress) or intranasal dopamine modified regional enzyme activity and ceramide levels, coinciding with rate of extinction. These data provide first evidence for a functional ASM–ceramide pathway in the brain involved in the extinction of learned behavior. This finding extends the known cellular mechanisms underlying behavioral plasticity to a new class of membrane‐located molecules, the sphingolipids, and their regulatory enzymes, and may offer new treatment targets for extinction‐ and learning‐related psychopathological conditions. Sphingolipids are common lipids in the brain which form lipid domains at pre‐ and postsynaptic membrane compartments. Here we show a decline in dorsal hippocampus ceramide species together with a reduction of acid sphingomyelinase activity during extinction of conditioned behavior in rats. This reduction was associated with expression of re‐learning‐related behavior, but not with emotional behaviors. Read theEditorial Highlight for this article on page485 . Abstract : Sphingolipids are common lipids in the brain which form lipid domains at pre‐ and postsynaptic membrane compartments. Here we show a decline in dorsal hippocampus ceramide species together with a reduction of acid sphingomyelinase activity during extinction of conditioned behavior in rats. This reduction was associated with expression of re‐learning‐related behavior, but not with emotional behaviors. Read theEditorial Highlight for this article on page485 .